Time-varying integration, the euro and international diversification strategies - Baele, Lieven; Inghelbrecht, Koen.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
This paper investigates the impact of globalization and integration on the relative benefits of country and industry diversification. Unlike previous models, our factor model allows asset exposures to vary with both structural changes and temporary fluctuations in the economic and financial environment. First, we find that globalization and integration have lead to a gradual convergence of country to industry betas, especially in Europe. Second, not accounting for time-varying factor exposures leads to substantial biases in measures of country and industry risk. Third, even though the edge has structurally decreased, geographical diversification continues being superior to industry diversification.
Economic Papers.